A gel-resistant positive electrode slurry and porous electrode preparation

By adjusting the amount and type of pore-forming agent, combined with the antigel positive electrode slurry and porous electrode preparation method, the problem of degradation of the electrode sheet under high compaction density is solved, and high porosity, good liquid retention and Electrode with long cycle life.

CN115241409BActive Publication Date: 2025-02-07WUHU ETC BATTERY LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211022633.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-25
Publication Date
2025-02-07
Estimated Expiration
2042-08-25

AI Technical Summary

Technical Problem

When the compaction density of existing lithium-ion battery electrodes is too high, the processing performance, liquid retention volume and wetting properties are affected, resulting in the deterioration of the high-rate performance and cycle life of the battery cell.

Method used

By changing the amount and type of pore-forming agent, the number of pores and structural stability of the electrode sheet is balanced, and the antigel positive electrode slurry and porous electrode preparation method is adopted, including mixing the positive electrode active material, conductive agent and binder, and adding organic The solvent and pore-forming agent were stirred and baked to prepare porous electrodes with high porosity and high liquid retention coefficient.

Benefits of technology

The porosity of the pole piece is improved, the liquid retention volume and electrical performance are improved, the cycle life of the battery cell is extended, and the slurry gel and film decomposition are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003814629610000061
    Figure BDA0003814629610000061
  • Figure BDA0003814629610000071
    Figure BDA0003814629610000071
Patent Text Reader

Abstract

The invention discloses a gel-resistant positive electrode slurry and porous electrode preparation. The positive electrode slurry in the invention gels slowly, and the surface and the inside of the electrode after drying have pores, which are helpful to increase the electrode liquid retention, improve the rate performance of the battery core, and reduce the polarization of the electrode. The invention uses glycolic acid, acetic acid, anhydrous oxalic acid, and anhydrous citric acid as pore formers. The pore formers are added after part of the organic solvent has been added to the stirring tank, which can avoid the corrosion of the tank body by the acidic pore former. The pore former can be miscible with N-methylpyrrolidone to ensure the uniformity of the dispersion of the pore former in the slurry. By controlling the drying temperature of the electrode, controlling the volatilization speed of glycolic acid and acetic acid and the decomposition speed of anhydrous oxalic acid and anhydrous citric acid, the porosity of the electrode is improved, and the structure of the electrode is ensured not to be destroyed. The pore former used in the present invention is a weakly acidic substance, which can neutralize the residual alkali on the surface of the positive electrode material, adjust the pH of the slurry, and has the effect of alleviating the gelation of the slurry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing an anti-gel positive electrode slurry and a porous electrode. Background Art

[0002] There are two main ways to increase the energy density of battery cells. On the one hand, you can use active materials with higher gram capacity. On the other hand, you can increase the coating weight of the pole piece and increase the compaction density of the pole piece. The compaction density of the pole piece is strongly correlated with the performance of the battery cell. Reasonable compaction density helps to reduce the contact impedance and AC impedance of the electrode and improve the electrochemical performance of the battery cell. However, when the compaction density is too high, the processing performance, liquid retention and wettability of the pole piece are affected. The high-rate performance and cycle life of the battery cell will deteriorate, and the surface temperature rise of the battery cell will increase. How to develop a battery cell with high energy density and long cycle life has become an urgent problem that the industry needs to solve.

[0003] Patents CN108417777B and CN105633350A reported the use of salts that are easily decomposed by heating, low-boiling organic solvents, etc. as pore-forming agents, the pore-forming agents are mixed with positive electrode materials for homogenization, and a porous electrode is obtained after coating and drying. This method utilizes the gas production during the decomposition of salts and the volatilization of organic solvents to form pores. This method has the advantage of uniform pore distribution, but inorganic salts such as ammonium bicarbonate, uric acid, and ammonium chloride will increase the pH of the slurry, accelerate the gelation of the slurry, and cause problems such as soft particles and scratches during coating.

[0004] Patent CN111490225B uses sulfur particles of uniform size as pore-forming agents, adds sulfur powder during mixing, and removes internal sulfur particles at high temperature after the electrode is dried. It has the advantage of controllable pore size, but needs to be coated twice, and the temperature for removing sulfur is relatively high (up to 200°C) and the time is >6h, which is not instructive in actual production. Summary of the invention

[0005] Technical problem to be solved by the present invention: The present invention proposes a method for preparing an anti-gel positive electrode slurry and a porous electrode. The slurry obtained by the method has the effect of preventing the slurry from gelling, and the electrode sheet after drying has the characteristics of high porosity and high liquid retention coefficient.

[0006] The present invention balances the number of electrode pores and the stability of the electrode structure by changing the amount and type of the pore-forming agent added, thereby avoiding film peeling and powder falling, and improving the liquid retention and electrical performance of the electrode.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] A method for preparing a porous electrode using an anti-gel positive electrode slurry, the specific steps are as follows:

[0009] S1: mixing and stirring a positive electrode active material, a conductive agent, and a binder; the positive electrode active material is one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and a ternary material;

[0010] S2: adding part of the organic solvent to the mixed material in S1 and stirring, the solid content of the slurry is 70-75wt%;

[0011] S3: adding pore-forming agent and remaining organic solvent, stirring and dispersing, at which time the solid content of the slurry is 62-70wt%;

[0012] S4: Increase the stirring and dispersing speed;

[0013] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0014] S6: Spread the slurry on aluminum foil and bake it at a temperature of 90-150° C. After baking, cool it to obtain a porous electrode.

[0015] Preferably, the ratio of the positive electrode active material, the conductive agent and the binder is 96-98:1-2:1-2.

[0016] Preferably, the conductive agent is one or more of conductive carbon black, acetylene black, carbon nanotubes, graphene, and Ketjen black.

[0017] Preferably, the binder is polyvinylidene fluoride; and the organic solvent is N-methylpyrrolidone.

[0018] Preferably, the pore-forming agent is one or more of glycolic acid, acetic acid, anhydrous oxalic acid, and anhydrous citric acid, and the amount of the pore-forming agent used is 0.5-2%wt of the total weight of the electrode material;

[0019] Preferably, in S1, the stirring revolution speed is 25-35rpm, the rotation speed is 500-800rpm, and the dispersion time is 30-60min; in S2, the stirring revolution speed is 10-25rpm, the rotation speed is 100-200rpm, and the dispersion time is 20-45min; in S3, the stirring revolution speed is 25-40rpm, the rotation speed is 500-800rpm, and the dispersion time is 40-60min; in S4, the stirring revolution speed is increased to 30-40rpm, the rotation speed is increased to 1500-1800rpm, and the dispersion time is 150-180min.

[0020] Preferably, in S6, the primary drying temperature of surface A is 90-105°C, and the secondary drying temperature is 115-130°C; the primary drying temperature of surface B is 90-105°C, and the secondary drying temperature is 125-150°C.

[0021] Beneficial effects obtained by the present invention:

[0022] The present invention uses glycolic acid, acetic acid, anhydrous oxalic acid and anhydrous citric acid as pore formers, and the pore formers are added after part of the organic solvent has been added to the stirring tank, so as to avoid the corrosion of the acidic pore formers to the tank body and reduce machine loss.

[0023] Hydroxyacetic acid and acetic acid are miscible with N-methylpyrrolidone, and anhydrous oxalic acid and anhydrous citric acid are easily soluble in N-methylpyrrolidone, ensuring the uniform dispersion of the pore former in the slurry. Hydroxyacetic acid and acetic acid have low boiling points, and a large number of bubbles are generated when volatilized at high temperatures to achieve pore formation. Anhydrous oxalic acid and anhydrous citric acid achieve pore formation by decomposing and producing gas. By controlling the drying temperature of the electrode, controlling the volatilization rate of hydroxyacetic acid and acetic acid, and the decomposition rate of anhydrous oxalic acid and anhydrous citric acid, the porosity of the electrode is improved, ensuring that the electrode structure is not destroyed. The pore former does not chemically react with the electrode material and has no effect on the electrical properties.

[0024] The pore-forming agent used in the present invention is a weakly acidic substance, which can neutralize the residual alkali on the surface of the positive electrode material, adjust the pH of the slurry, and alleviate the gelation of the slurry. It effectively reduces soft particles and scratches in the slurry, which helps to improve production capacity and quality rate. The pore-forming agent absorbed into the material by capillary action during the homogenization process cannot be completely volatilized by short-term drying at normal pressure. The residual acidic substance can effectively inhibit the Fe in lithium iron phosphate. 2+ After being oxidized, the lithium iron phosphate electrode exhibits smaller impedance, higher reversible capacity and better cycle stability.

[0025] The present invention obtains a pole piece porosity of 29-49%, and the pore structure is evenly distributed, which can increase the liquid retention of the pole piece, and there is sufficient electrolyte during the battery cell cycle, thereby ensuring the rate performance and cycle life of the battery cell. DETAILED DESCRIPTION

[0026] The specific implementation modes of the present invention are further explained in detail below through the description of embodiments, so as to help those skilled in the art to have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention.

[0027] Example 1: Prepare a porous electrode sheet as follows:

[0028] S1: 97 parts of lithium iron phosphate, 1 part of conductive carbon black, and 2 parts of polyvinylidene fluoride were mixed and stirred at an orbital speed of 25 rpm, an autorotation speed of 800 rpm, and a dispersion time of 30 min; wherein the polyvinylidene fluoride was used as a binder. The stirring device used in the embodiments of the present invention is a double-dispersing-shaft double-planetary mixer.

[0029] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 15 rpm, the rotation of 100 rpm, the dispersion time of 20 min, and the solid content of the slurry of 70-75 wt%;

[0030] S3: Add 0.5 parts of glycolic acid and the remaining N-methylpyrrolidone, stir and disperse, the revolution is 40 rpm, the rotation is 600 rpm, and the dispersion time is 40 min. At this time, the solid content of the slurry is 62-70wt%.

[0031] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1500 rpm, and the dispersion time to 150 min;

[0032] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0033] S6: The slurry is coated on aluminum foil, the first-level drying temperature of the A side is 95°C, and the second-level drying temperature is 130°C; the first-level drying temperature of the B side is 95°C, and the second-level drying temperature is 135°C, to obtain a porous electrode.

[0034] Example 2: Prepare a porous electrode sheet as follows:

[0035] S1: 97.5 parts of lithium iron phosphate, 1 part of acetylene black, and 1.5 parts of polyvinylidene fluoride were mixed and stirred at an orbital speed of 25 rpm and an autorotation speed of 800 rpm for a dispersion time of 30 min;

[0036] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 15 rpm and the rotation of 100 rpm. The dispersion time is 20 min, and the solid content of the slurry is 70-75 wt%;

[0037] S3: Add 1 part of acetic acid and the remaining N-methylpyrrolidone, stir and disperse, the revolution is 25 rpm, the rotation is 600 rpm, and the dispersion time is 60 min. At this time, the solid content of the slurry is 62-70wt%.

[0038] S4: Increase the revolution speed to 40 rpm, the rotation speed to 1800 rpm, and the dispersion time to 150 min;

[0039] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0040] S6: The slurry is coated on aluminum foil, the first-level drying temperature of the A side is 95°C, and the second-level drying temperature is 126°C; the first-level drying temperature of the B side is 100°C, and the second-level drying temperature is 135°C, to obtain a porous electrode.

[0041] Example 3: Prepare a porous electrode sheet as follows:

[0042] S1: 96 parts of lithium iron phosphate, 2 parts of Ketjen black, and 2 parts of polyvinylidene fluoride were mixed and stirred at a revolution of 25 rpm and a rotation of 800 rpm for 30 min.

[0043] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 15 rpm, the rotation of 100 rpm, the dispersion time of 20 min, and the solid content of the slurry of 70-75 wt%;

[0044] S3: Add 1 part of anhydrous oxalic acid and the remaining N-methylpyrrolidone, stir and disperse, the revolution is 25 rpm, the rotation is 800 rpm, and the dispersion time is 40 min. At this time, the solid content of the slurry is 62-70wt%.

[0045] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1500 rpm, and the dispersion time to 180 min;

[0046] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0047] S6: The slurry is coated on aluminum foil, the first-level drying temperature of the A side is 100°C, and the second-level drying temperature is 130°C; the first-level drying temperature of the B side is 105°C, and the second-level drying temperature is 145°C, to obtain a porous electrode.

[0048] Example 4: Prepare a porous electrode sheet as follows:

[0049] S1: 97 parts of lithium iron phosphate, 1 part of conductive carbon black, and 2 parts of polyvinylidene fluoride were mixed and stirred at an orbital speed of 25 rpm and an autorotation speed of 800 rpm for a dispersion time of 30 min;

[0050] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 15 rpm, the rotation of 100 rpm, the dispersion time of 20 min, and the solid content of the slurry of 70-75 wt%;

[0051] S3: Add 0.5 parts of anhydrous citric acid and the remaining N-methylpyrrolidone, stir and disperse, the revolution is 25 rpm, the rotation is 600 rpm, and the dispersion time is 40 min. At this time, the solid content of the slurry is 62-70wt%.

[0052] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1500 rpm, and the dispersion time to 150 min;

[0053] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0054] S6: The slurry is coated on aluminum foil, the first-level drying temperature of the A side is 100°C, and the second-level drying temperature is 130°C; the first-level drying temperature of the B side is 105°C, and the second-level drying temperature is 150°C, to obtain a porous electrode.

[0055] Example 5: Prepare a porous electrode sheet as follows:

[0056] S1: 98 parts of lithium cobalt oxide, 1 part of conductive carbon black, and 1 part of polyvinylidene fluoride were mixed and stirred at a revolution of 35 rpm and a rotation of 500 rpm for 60 min.

[0057] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 10 rpm, the rotation of 200 rpm, the dispersion time of 30 min, and the solid content of the slurry of 70-75 wt%;

[0058] S3: Add 0.5 parts of glycolic acid and the remaining N-methylpyrrolidone, stir and disperse, the revolution is 35 rpm, the rotation is 500 rpm, and the dispersion time is 40 min. At this time, the solid content of the slurry is 62-70wt%.

[0059] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1500 rpm, and the dispersion time to 150 min;

[0060] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0061] S6: The slurry is coated on aluminum foil, and the primary drying temperature of the A side is 95°C, and the secondary drying temperature is 130°C; the primary drying temperature of the B side is 95°C, and the secondary drying temperature is 135°C, to obtain a porous electrode.

[0062] Example 6: Prepare a porous electrode sheet as follows:

[0063] S1: 97.5 parts of lithium cobalt oxide, 0.8 parts of carbon nanotubes, and 1.7 parts of polyvinylidene fluoride were mixed and stirred at an orbital speed of 25 rpm and an autorotation speed of 800 rpm for a dispersion time of 30 min;

[0064] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 15 rpm, the rotation of 100 rpm, the dispersion time of 20 min, and the solid content of the slurry of 70-75 wt%;

[0065] S3: Add 1 part of acetic acid and the remaining N-methylpyrrolidone, stir and disperse, the revolution is 25 rpm, the rotation is 600 rpm, and the dispersion time is 60 min. At this time, the solid content of the slurry is 62-70wt%.

[0066] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1800 rpm, and the dispersion time to 150 min;

[0067] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0068] S6: The slurry is coated on aluminum foil, the first-level drying temperature of the A side is 95°C, and the second-level drying temperature is 126°C; the first-level drying temperature of the B side is 100°C, and the second-level drying temperature is 135°C, to obtain a porous electrode.

[0069] Example 7: Prepare a porous electrode sheet as follows:

[0070] S1: 98 parts of ternary material, 0.5 parts of graphene, and 1.5 parts of polyvinylidene fluoride were mixed and stirred at an orbital speed of 25 rpm and an autorotation speed of 800 rpm for a dispersion time of 30 min;

[0071] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution speed of 25 rpm and the rotation speed of 100 rpm. The dispersion time is 20 min, and the solid content of the slurry is 70-75 wt%;

[0072] S3: Add 1 part of anhydrous oxalic acid and the remaining N-methylpyrrolidone, stir and disperse, the revolution is 25 rpm, the rotation is 600 rpm, and the dispersion time is 40 min. At this time, the solid content of the slurry is 62-70wt%.

[0073] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1500 rpm, and the dispersion time to 150 min;

[0074] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0075] S6: The slurry is coated on aluminum foil, the first-level drying temperature of the A side is 100°C, and the second-level drying temperature is 130°C; the first-level drying temperature of the B side is 105°C, and the second-level drying temperature is 145°C, to obtain a porous electrode.

[0076] Example 8: Prepare a porous electrode sheet as follows:

[0077] S1: 98 parts of lithium manganate, 1 part of conductive carbon black and 1 part of polyvinylidene fluoride were mixed and stirred at an orbital speed of 25 rpm and an autorotation speed of 800 rpm for 30 min.

[0078] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 15 rpm, the rotation of 100 rpm, the dispersion time of 20 min, and the solid content of the slurry of 70-75 wt%;

[0079] S3: Add 0.5 parts of anhydrous citric acid and the remaining N-methylpyrrolidone, stir and disperse, the revolution is 25 rpm, the rotation is 600 rpm, and the dispersion time is 40 min. At this time, the solid content of the slurry is 62-70wt%.

[0080] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1500 rpm, and the dispersion time to 150 min;

[0081] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0082] S6: The slurry is coated on aluminum foil, the first-level drying temperature of the A side is 100°C, and the second-level drying temperature is 130°C; the first-level drying temperature of the B side is 105°C, and the second-level drying temperature is 150°C, to obtain a porous electrode.

[0083] Comparative Example 1: A porous electrode sheet was prepared as follows:

[0084] S1: 97 parts of lithium iron phosphate, 1 part of conductive carbon black, and 2 parts of polyvinylidene fluoride were mixed and stirred at an orbital speed of 25 rpm and an autorotation speed of 800 rpm for a dispersion time of 30 min;

[0085] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 15 rpm and the rotation of 100 rpm. The dispersion time is 20 min, and the solid content of the slurry is 70-75 wt%;

[0086] S3: Add the remaining N-methylpyrrolidone, stir and disperse, the revolution is 25 rpm, the rotation is 600 rpm, and the dispersion time is 40 min. At this time, the solid content of the slurry is 62-70wt%.

[0087] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1500 rpm, and the dispersion time to 150 min;

[0088] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0089] S6: The slurry is coated on aluminum foil, the first-level drying temperature of the A side is 95°C, and the second-level drying temperature is 130°C; the first-level drying temperature of the B side is 95°C, and the second-level drying temperature is 135°C, to obtain a porous electrode.

[0090] Comparative Example 2: A porous electrode sheet was prepared as follows:

[0091] S1: 98 parts of lithium cobalt oxide, 1 part of conductive carbon black, and 1 part of polyvinylidene fluoride were mixed and stirred at a revolution of 35 rpm and a rotation of 500 rpm for 60 min.

[0092] S2: Add part of N-methylpyrrolidone to the mixed material in S1 and stir, with the revolution of 10 rpm, the rotation of 200 rpm, the dispersion time of 30 min, and the solid content of the slurry of 70-75 wt%;

[0093] S3: Add the remaining N-methylpyrrolidone, stir and disperse, the revolution is 35 rpm, the rotation is 500 rpm, and the dispersion time is 40 min. At this time, the solid content of the slurry is 62-70wt%.

[0094] S4: Increase the revolution speed to 30 rpm, the rotation speed to 1500 rpm, and the dispersion time to 150 min;

[0095] S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating;

[0096] S6: The slurry is coated on aluminum foil, and the primary drying temperature of the A side is 95°C, and the secondary drying temperature is 130°C; the primary drying temperature of the B side is 95°C, and the secondary drying temperature is 135°C, to obtain a porous electrode.

[0097] Set the compaction density to 2.5 g / cm 3 The pole pieces obtained in Examples 1-4 and Control Example 1 were rolled, and the porosity and liquid absorption of the pole pieces were tested. The results are shown in the following table.

[0098] Table 1 Results of the determination of the electrode porosity and liquid absorption at lower compaction density

[0099]

[0100]

[0101] Set the compaction density to 4.2 g / cm 3 The pole pieces obtained in Examples 5-8 and Comparative Example 2 were rolled, and the porosity and liquid absorption of the pole pieces were tested. The results are shown in the following table.

[0102] Table 2 Results of the electrode porosity and liquid absorption at higher compaction density

[0103] Group Pole piece porosity % Liquid absorption / g Example 5 21.9 2.5 Example 6 21.3 2.4 Example 7 19.5 2.1 Example 8 18.8 1.9 Comparative Example 2 14.5 1.5

[0104] The above results show that adding pore-forming agent can increase the porosity of the electrode, increase the liquid retention, facilitate electrode infiltration, and help improve the rate performance and cycle life of the battery cell.

[0105] Applying the above method to lithium manganese oxide and ternary materials can also achieve similar benefits, and has the effect of improving the porosity and liquid absorption of lithium manganese oxide pole pieces and ternary material pole pieces.

[0106] The above embodiments are only for illustrating the technical idea of ​​the present invention, and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the present invention; any technology not involved in the present invention can be realized by existing technologies.

Claims

1. A method for preparing a porous electrode using an anti-gel positive electrode slurry, characterized in that: The specific steps are as follows: S1: mixing and stirring a positive electrode active material, a conductive agent, and a binder; the positive electrode active material is one of lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide, and a ternary material; S2: adding part of the organic solvent to the mixed material in S1 and stirring, the solid content of the slurry is 70-75wt%; S3: adding pore-forming agent and remaining organic solvent, stirring and dispersing, at which time the solid content of the slurry is 62-70wt%; S4: Increase the stirring and dispersing speed; S5: Reverse to remove bubbles, and put the slurry into the buffer tank for slow stirring and coating; S6: coating the slurry on aluminum foil and baking it at a temperature of 90-150° C., and cooling it after baking to obtain a porous electrode; The pore-forming agent is one or more of glycolic acid, acetic acid, anhydrous oxalic acid, and anhydrous citric acid, and the amount of the pore-forming agent used is 0.5 to 2 wt% of the total weight of the electrode material; In the S1, the stirring revolution speed is 25-35rpm, the rotation speed is 500-800rpm, and the dispersion time is 30-60min; in the S2, the stirring revolution speed is 10-25rpm, the rotation speed is 100-200rpm, and the dispersion time is 20-45min; in the S3, the stirring revolution speed is 25-40rpm, the rotation speed is 500-800rpm, and the dispersion time is 40-60min; in the S4, the stirring revolution speed is increased to 30-40rpm, the rotation speed is increased to 1500-1800rpm, and the dispersion time is 150-180min; In the S6, the primary drying temperature of the A surface is 90-105°C, and the secondary drying temperature is 115-130°C; the primary drying temperature of the B surface is 90-105°C, and the secondary drying temperature is 125-150°C.

2. A method for preparing a porous electrode using an anti-gel positive electrode slurry according to claim 1, characterized in that: The positive electrode active material, the conductive agent, and the binder account for 96-98:1-2:1-2.

3. The method for preparing a porous electrode using an anti-gel positive electrode slurry according to claim 1, characterized in that: The conductive agent is one or more of conductive carbon black, acetylene black, carbon nanotubes, graphene, and Ketjen black.

4. The method for preparing a porous electrode using an anti-gel positive electrode slurry according to claim 1, characterized in that: The binder is polyvinylidene fluoride; and the organic solvent is N-methylpyrrolidone.

Citation Information

Patent Citations

  • Porous pole piece and preparation method thereof and lithium ion battery

    CN105633350A

  • A porous ternary composite cathode sheet, its preparation method and its application

    CN108417777B

  • Cathode piece of lithium ion battery and preparation method of cathode piece

    CN108336300A

  • A preparation method of a porous lithium ion electrode sheet with high energy density and a lithium ion battery

    CN109167020A